PENGARUH ANALISA SWOT DAN SEGMENTASI PASAR TERHADAP PENCAPAIAN TARGET PENJUALAN DI PT. SELTECH UTAMA MANDIRI - Richard Richard; Thomas Sumarsan Goh; Errie Margery (JURNAL BISNIS KOLEGA, 2018)
The purpose of this study is to analyze the influence of swot analysis toward the achievement of the sales target, to analyze the influence of market segmentation toward the achievement of the sales target and to analyze the influence of swot analysis and market segmentation toward the achievement of the sales target.Â  The method used in this study is a survey approach, the type of research is quantitative descriptive, and the characteristic of research is explanatory research. The population of this research is all employees at PT. Seltech Utama Mandiri with a population of 45 persons and the samples are 45 persons. The methods of collecting data are interviews, distribution of questionnaires, and documentary studies. The variables are examined with a Likert scale. The model analysis of the data used to answer the hypothesis is multiple regressions. Research result indicates swot analysis and market segmentation jointly and significantly affect on the achievement of the sales target at PT. Seltech Utama Mandiri, and partially Â Keywords: SWOT Analysis, Market Segmentation, Target Sales Achievement